2014
DOI: 10.1364/oe.22.013366
|View full text |Cite
|
Sign up to set email alerts
|

Generation of mode-locked optical pulses at 1035 nm from a fiber Bragg grating stabilized semiconductor laser diode

Abstract: Abstract:We report the generation of transform-limited, ~18 ps optical pulses from a fiber Bragg grating (FBG) stabilized semiconductor laser diode. Up to 7.2 pJ of pulse energy and a peak power of 400mW were achieved when operating at a repetition frequency of 832.6 MHz, a multiple of the cavity (diode + FBG) free spectral range (FSR). A small detuning in the repetition frequency resulted in broader optical pulses. We have shown experimentally the transition from a gain-switched regime of operation to mode-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Although the source in [115] lacked inter-pulse coherence-a hallmark trait of modelocked oscillators, and a necessary one in comb-based applications-there is some evidence that even that feature might not be out of reach. Self-seeded gain-switched diodes have been shown to exhibit inter-pulse coherence [137], and an interesting question is whether injection seeding can accomplish the same. Given that gain-switched diodes have been shown to inherit coherence from an externally-seeding, pulsed, master laser, it seems plausible that an external CW seed might likewise confer inter-pulse coherence [138].…”
Section: Prospects For Short Pulses Without Mode-locking: Multi-stagementioning
confidence: 99%
“…Although the source in [115] lacked inter-pulse coherence-a hallmark trait of modelocked oscillators, and a necessary one in comb-based applications-there is some evidence that even that feature might not be out of reach. Self-seeded gain-switched diodes have been shown to exhibit inter-pulse coherence [137], and an interesting question is whether injection seeding can accomplish the same. Given that gain-switched diodes have been shown to inherit coherence from an externally-seeding, pulsed, master laser, it seems plausible that an external CW seed might likewise confer inter-pulse coherence [138].…”
Section: Prospects For Short Pulses Without Mode-locking: Multi-stagementioning
confidence: 99%
“…In the same year, Teh et al [48] reported transform-limited laser pulses of about 18 ps from FBG-ECSL. The SMSR of the laser was 50 dB, and the maximum wavelength offset was 0.1 nm.…”
Section: Fbg-ecslsmentioning
confidence: 99%
“…We furthermore measure the single-pulse spectra using the dispersive Fourier transform technique [26], and confirm that the distributions of the pulses and their energies are not heavytailed, nor are the averages strongly skewed by extreme outliers (see Appendix B). Finally, techniques such as self-seeding [27][28][29] and external injection [30,31] have been thoroughly investigated as ways of curtailing shot-to-shot fluctuations in GSDs, reducing timing jitter, or even creating interpulse coherence [32]. We expect that implementing these approaches in a similar system to ours will yield comparable noise reductions, making such systems viable alternatives to modelocked oscillators even for noise-or coherencesensitive applications.…”
mentioning
confidence: 95%